EVALUASI PROGRAM PENDAMPINGAN PEMBUATAN PERANGKAT CUCI TANGAN OTOMATIS DALAM UPAYA MITIGASI COVID-19 DI SULAWESI TENGGARA - Hasmina Tari Mokui; Luther Pagiling; Tachrir Tachrir; Ranno Marlany Rachman (Universitas Halu Oleo, 2021)
The number of positive cases of COVID-19 has continued to increase since it was announced by the Government in early March 2020. According to the World Health Organization (WHO), the provision of hygiene and sanitation facilities is one of the most important means of mitigating the outbreak of COVID-19 and other infectious diseases. This study aims to evaluate the socialization of assistance in making automatic handwashing devices online to communities in Southeast Sulawesi as an effort to mitigate COVID-19. The socialization was carried out by collaborating with the Southeast Sulawesi COVID-19 SATGAS Secretariat as a display location for a prototype automatic hand washing device. Meanwhile, assistance is carried out through the implementation of webinars via Zoom and the publication of video tutorials on social media in the form of YouTube and other media. The performance evaluation of the mentoring program is carried out in two forms, namely searches on online media and through online feedback presented after the webinar. Based on the response from online media and the feedback, the public responded positively to this and some of them were interested in making similar hand washing devices.